Changes in Nutrient Plant Availability in Loam and Sandy Clay Loam Soils after Wood Fly and Bottom Ash Amendment. (1st March 2016) - Ochecova, Pavla; Tlustos, Pavel; Szakova, Jirina; Mercl, Filip; Maciak, Matus
Abstract : Wood ash has the potential to be an auxiliary fertilizing material. The effect of growing application of the ash derived from woody biomass (representing both fly and bottom ash) on Ca, K, P, and Mg to plant availability in four soils (two loam and two sandy clay loam soils) was investigated. Additives were applied to soils at two rates (1 and 5% w/w) and incubated for 0, 14, 28, and 56 d. Plant‐available element concentrations extractable via Mehlich 3 solution were determined using flame atomic absorption spectrometry (F‐AAS) and inductively coupled plasma–optical emission spectrometry (ICP–OES). The ashes were also characterized using x‐ray diffraction (XRD). The results, supported by the statistical linear mixed‐effect model, indicated the significant increase of plant‐available nutrient portions in all soils with an increasing ash rate. In addition, the other factors, such as incubation time and soil properties (especially pH, content of clay, and organic C), determined nutrient plant availability in our experiment. In the case of Ca, clay content was a more determining factor for plant availability than organic C content in soils. Concretely, the decrease of plant‐available Ca after ash enrichment was slower in soils with a high clay content than in soils with a high organic C content. Based on our results, wood ash should be applied on soils at least in rate 5% w/w and soils should be characterized before ash addition for the best wood ash fertilizing effect.